Eksperimen Gangguan Getaran Pada Fenomena Cloaking Cahaya Tampak Sistem Empat Lensa - Okky Fajar Tri Maryana; L. Y. Ginting; F. Pahlawan; M. Y. Darmawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Creating optical illusions or invisible objects by using cloaking devices is still being a concern for many researchers in the world. The cloaking devices are working in visible spectrum regime, large dimention, and replicable. Addition with the full-field of light, no new materials, simple infrastructure, and scale easily may be considered an ‘ideal’ cloaking device. Based on four lenses cloaking system by Choi’s work shows an idea for solution of blindspot large vehicle’s problem. The set up for this optical system is regular covex lenses non-aberation based on educational laboratory framework. The experimental confirmation that cloaking area with 4f convex lenses is limited to certain areas only, not 100 % of the object to be observed can disappear from the view. Vibration disturbance generated by rotor module (wheels disturbance analogy on vehicles) applied on the system demonstrate that below on 2000 rotation per minutes (rpm) equal 33.34 hertz, optical illusion is still consistent. The results support the information to create optical cloaking prototype for optimizing large vehicle driver’s visibility as alternative solution blindspot’s problem.